SOSIALISASI DAN PELATIHAN PEMANFAATAN LIMBAH AIR KELAPA MENJADI PRODUK NATA DE COCO DI DESA KEMBANG KERANG - Arini, Naura Nazhyrah; Sarkono; Fahriansyah, Ridho; Amalia, Rizka Ayu; Putrini, Andini Justina; Mulyanugroho, Ade Isna; Muhanna, Arqan Doni; Asniwati; Risnawati; Wahyuningsih; Pratama, Muhammad Alif (Jurnal Wicara, 2024)
Kembang Kerang Village, located in the East Lombok Regency of West Nusa Tenggara's Aikmel District, has a wealth of agricultural potential, particularly in the plantation industry, specifically in the coconut commodities. A frequently underutilized byproduct that pollutes the environment is coconut water. By teaching and enabling community members—particularly organizations like PKK and KWT—to produce Nata de Coco from coconut water, this article offers an innovative alternative. The workshop, which took place in the village of Kembang Kerang, focused on how important it is to use discarded coconut water to lessen environmental damage and boost economic value. The training approach guarantees that participants may independently create and market the product through socialization, counseling, practice, and direct help in the creation of Nata de Coco. The following article guides readers through the entire process of creating Nata de Coco, from preparing the beginning to packaging. Rich in fiber and healthy nutrients, what follows Nata de Coco is made. To conclude, community creativity and abilities in turning coconut water waste into a viable economic venture have to be enhanced through training and outreach programs. A strong response to the training session's enthusiasm was displayed by the participants, which created opportunities for the village's coconut products to thrive sustainably and economically.